PENGARUH FINANCIAL DISTRESS, KEMAMPUAN MANAJERIAL DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE - Alamanda Rizka Hasanah (2022)
This study aims to examine and analyze the effect of financial distress, managerial ability and audit committee on tax avoidance in manufacturing sector companies in Indonesia. Data were obtained from 149 financial statements of companies listed on the Indonesia Stock Exchange. Panel data regression with random effects model was used to test and analyze the data. The results showed that there was a negative effect between financial difficulties and managerial ability on tax avoidance, but there was no influence between the audit committee on tax avoidance. As for the control variable, there is a positive influence between profitability on tax avoidance and there is no influence between leverage on tax avoidance.